1973
DOI: 10.1037/h0035754
|View full text |Cite
|
Sign up to set email alerts
|

The desegregation of clinical psychology training.

Abstract: Studied the success of the American Psychological Association in encouraging minority participation in psychology. A questionnaire similar to a 1970 instrument by R. Boxley and N. N. Wagner was sent to the 144 programs offering doctorates in clinical psychology. From an 80% return, results indicate that (a) no significant (p < .01) increase has occurred in student or faculty representation and (b) minority groups as a whole are underrepresented on faculties (p < .001). 75.5% of those responding make special ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Boxley & Wagner (1971) found that in the clinical programs surveyed, most of the clinical service training was performed in white middle-class mental health agencies. Padilla et al (1973) also found that graduate clinical training programs were limited in breadth with respect to the inclusion of culturally relevant materials in their curricula. The findings of Bernal & Padilla (1982) indicate that while most clinical training programs agreed with the need to include culturally relevant materials, most were reluctant to do so.…”
mentioning
confidence: 99%
“…Boxley & Wagner (1971) found that in the clinical programs surveyed, most of the clinical service training was performed in white middle-class mental health agencies. Padilla et al (1973) also found that graduate clinical training programs were limited in breadth with respect to the inclusion of culturally relevant materials in their curricula. The findings of Bernal & Padilla (1982) indicate that while most clinical training programs agreed with the need to include culturally relevant materials, most were reluctant to do so.…”
mentioning
confidence: 99%
“…Evidence of representational inequity has been reported consistently (Albee, 1969;Boxly & Wagner, 1971;Kennedy & Wagner, 1979;A. Padilla & Ruiz, 1973;E. Padilla, Boxley, & Wagner, 1973;Parham & Moreland, 1981;Suber, 1977;Wispe et aL, 1969).…”
mentioning
confidence: 96%
“…Minority underrepresentation in applied psychology has been documented. Native Americans, Asian Americans, blacks, and Hispanics are seriously underrepresented as both students and faculty members in clinical psychology programs (Boxley & Wagner, 1971; Kennedy & Wagner, 1979; Padilla, Boxley, & Wagner, 1973). In 1980, only 5.5% of the faculty in clinical psychology programs and 6.8% of the faculty in counseling psychology programs were ethnic minorities (Russo, Olmedo, Stapp, & Fulcher, 1981).…”
mentioning
confidence: 99%